MENINGKATKAN ECOLITERACY SISWA SD MELALUI METODE FIELD-TRIP KEGIATAN EKONOMI PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL - Nugraha, Rana Gustian (Mimbar Sekolah Dasar, 2015)
The purpose of this research is to improve ecoliteracy students through field-trip method of the impact upon economic activity in the form of waste tahu. This study uses observations in the form of the method field-trip to the factory tahu and the school environment. The method used in this research is Classroom Action Research (classroom action research) in the fourth-grade students of SDN Lembur Situ , North Sumedang. Ecoliteracy indicator of this research is to use an indicator of Thomas Lickona (2012) in which there are knowledge aspect, awareness and application. The research instrument used was direct observation of a student observation sheets, questionnaires, student worksheets, test tool evaluation and field record sheets were used to obtain data through records in a form and format that checklist done by the author and our partners as an observer. Implementation of classroom action research was conducted three cycles. Results from this study are the increased understanding, awareness and application of students to ecoliteracy.Keywords: ecoliteracy, field-trip, economic, IPS, SD.